Empowering educators and students through contextualized global citizenship for sustainable development - Erwin B. Berry; El Dixon G. Plazo; Ofelia L. Correos (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study explores how educators and students in Philippine secondary schools conceptualize global citizenship education (GCE) and understand their roles in advancing the sustainable development goals (SDGs). Despite its prominence in global education agendas, GCE remains inconsistently understood across local contexts. Using a qualitative research design, in-depth interviews were conducted with 21 teachers and students in Surigao del Sur. Thematic analysis revealed seven interconnected themes: i) holistic education: framing global citizenship beyond academics; ii) cultural sensitivity and respect for diversity; iii) active engagement and global awareness; iv) education as a channel for sustainable development; v) becoming a global citizen as a personal journey; vi) technology and global connectivity; and vii) teaching values for global responsibility. Findings indicate that while both groups support GCE, their interpretations are shaped by lived experiences, institutional conditions, and cultural environments. Teachers highlighted intentional instruction and moral formation, whereas students emphasized identity development, participation, and global awareness. However, gaps remain in critical reflection and structural understanding. In response, this study introduces the contextualized empowerment framework, a strategic model that integrates civic action, values, identity, and digital literacy to guide localized and ethical implementation of GCE. The framework offers actionable insights for curriculum development, teacher training, and educational policy reforms.